Ghana Priorities for Ending Poverty and Boosting Shared Prosperity : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
The objective of this Systematic Country Diagnostic (SCD) is to demonstrate the current development challenges and opportunities facing Ghana, and offer a set of priority areas of intervention to accelerate economic growth and achieve the twin goals of ending extreme poverty and boosting shared prosperity.